2016
DOI: 10.15252/embr.201540970
|View full text |Cite
|
Sign up to set email alerts
|

miR‐515‐5p controls cancer cell migration throughMARK4 regulation

Abstract: Here, we show that miR‐515‐5p inhibits cancer cell migration and metastasis. RNA‐seq analyses of both oestrogen receptor receptor‐positive and receptor‐negative breast cancer cells overexpressing miR‐515‐5p reveal down‐regulation of NRAS, FZD4, CDC42BPA, PIK3C2B and MARK4 mRNAs. We demonstrate that miR‐515‐5p inhibits MARK4 directly 3′ UTR interaction and that MARK4 knock‐down mimics the effect of miR‐515‐5p on breast and lung cancer cell migration. MARK4 overexpression rescues the inhibitory effects of miR‐51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 25 publications
5
81
0
Order By: Relevance
“…5b and c). Simultaneously, we noticed that one of these candidate miRNAs, miR-515-5p, has been found to dramatically inhibit breast cancer cell proliferation and to control cancer cell migration through MARK4 regulation in breast cancer [42,43]. Therefore, we examined whether LINC00673 could interact with miR-515-5p to regulate MARK4.…”
Section: Linc00673 Regulates Mark4 Expression By Competing For Mir-51mentioning
confidence: 99%
“…5b and c). Simultaneously, we noticed that one of these candidate miRNAs, miR-515-5p, has been found to dramatically inhibit breast cancer cell proliferation and to control cancer cell migration through MARK4 regulation in breast cancer [42,43]. Therefore, we examined whether LINC00673 could interact with miR-515-5p to regulate MARK4.…”
Section: Linc00673 Regulates Mark4 Expression By Competing For Mir-51mentioning
confidence: 99%
“…Previous studies have uncovered the anti‐carcinogenic role of miR‐450b‐5p and miR‐515‐5p in some cancers, including in lung cancer 24‐27. Nonetheless, their specific functions in LUSC cells are still unclear, so we tested the effects of miR‐450b‐5p and miR‐515‐5p in LUSC cells.…”
Section: Resultsmentioning
confidence: 99%
“…There have also been multiple reports on the role of miR‐486 in tumorigenesis, some concluding that it acts as a tumor suppressor of LUSC . miR‐515 has also been reported as a tumor suppressor, and similarly, studies have shown that miR‐512 not only inhibits glycolysis but also accelerates apoptosis . So far, there are few reports of a role for miR‐516 or miR‐525 in LUSC, however, there is evidence that they can regulate target genes in other tumors to affect protein expression .…”
Section: Discussionmentioning
confidence: 99%